In Vivo and In Vitro Evaluation of Pharmacological Potentials of Secondary Bioactive Metabolites of Dalbergia candenatensis Leaves. (26th December 2017) - Anisuzzman, Md.; Hasan, Md. Mahedi; Acharzo, Amit Kumar; Das, Asish Kumar; Rahman, Sinthia
Abstract : Background. Dalbergia species has wide range of secondary metabolites and is traditionally used in treatment of painful micturition, swelling, and leprosy and as blood tonic. The study evaluates membrane stabilizing, anticoagulant, analgesic, cytotoxic, subacute anti-inflammatory, and depression potentials of D. candenatensis leaves metabolites. Methods . Membrane stabilizing activity was evaluated by hypotonic induced hemolysis assay, whereas anticoagulant activity is done through extrinsic pathway by measuring prothrombin time. Analgesic action, cytotoxic effect, and subacute anti-inflammatory activity were determined by acetic acid induced writhing model, brine shrimp lethality bioassay, and formaldehyde induced model, respectively. Depression activity was measured by the Open Field, Hole Cross, Hole Board, and thiopentone induced sleeping time measuring methods. Results . D. candenatensis contains phenolic, flavonoid, and tannin, quantified as 416.25 mg, 330.00 mg, and 432.22 mg Gallic Acid Equivalent/100 g of dry extract, respectively. Extract showed maximum inhibition of writhe, hemolysis, and edema, approximate to 57.14%, 36.62%, and 34.1%, respectively. LC50 value for nauplii was 151.499 μ g/ml. Mean prothrombin time was approximate to 31.0 ± 2.31 seconds at 1.0 mg/ml. Extract showed depression activity, and maximum sleeping time was noted to be about 141 minutes. Conclusion . D. candenatensis leaves show dose dependent membrane stabilizing, anticoagulant, depression, analgesic, moderate cytotoxic, and subacute anti-inflammatory activities.